Long Non-coding Antisense RNA TNRC6C-AS1 Is Activated in Papillary Thyroid Cancer and Promotes Cancer Progression by Suppressing TNRC6C Expression - Muhanhali, Dilidaer; Zhai, Tianyu; Jiang, Jingjing; Ai, Zhilong; Zhu, Wei; Ling, Yan (Frontiers in Endocrinology, 2018)
Context: Evidences have shown the important role of long non-coding antisense RNAs in regulating its cognate sense gene in cancer biology. Objective: Investigate the regulatory role of a long non-coding antisense RNA TNRC6C-AS1 on its sense partner TNRC6C, and their effects on the aggressiveness and iodine-uptake ability of papillary thyroid cancer (PTC). Design: TNRC6C-AS1 was identified as the target long non-coding RNA in PTC by using microarray analysis and computational analysis. In vitro gain/loss-of-function experiments were performed to investigate the effects of TNRC6C-AS1 and TNRC6C on proliferation, apoptosis, migration, invasion and iodine-uptake ability of TPC1 cells. Expression levels of TNRC6C-AS1 and TNRC6C of 30 cases of PTC tissues and its adjacent normal thyroid tissues were determined. Results: Downregulation of TNRC6C-AS1 or overexpression of TNRC6C inhibited proliferation, migration and invasion of TPC1 cells, while apoptosis and iodine uptake was promoted in TPC1 cells. Suppression of TNRC6C-AS1 significantly increased the expression of TNRC6C in TPC1 cells. The inhibitory effect of TNRC6C-AS1 knockdown on cell proliferation, migration and invasion was attenuated when the expression of TNRC6C was suppressed simultaneously, indicating TNRC6C is a functional target of TNRC6C-AS1. The expression of TNRC6C-AS1 was significantly higher, while the TNRC6C mRNA and protein were significantly lower in PTC tissues than normal adjacent tissues. There was a significant inverse correlation between TNRC6C-AS1 and TNRC6C mRNA in PTC tissue samples. Conclusion: TNRC6C-AS1 promotes the progression of PTC and inhibits its ability of iodine accumulation by suppressing the expression of TNRC6C. Targeting TNRC6C-AS1 - TNRC6C axis may be a new promising treatment for PTC.